OPERATION TECHNIQUE OF ANTERIOR MENINGOENCEPHALOCELE: Transcranial Combined with Anterior Resection (Case Report) - Muhammad-Zafrullah, A.; Yudoyono, F.; Mirna-Sobana, A.; Faried, and A. (BALI MEDICAL JOURNAL; Volume 2 Number 2, May-August 2013)
Meningoencephaloceles are a frequent condition characterized by protrusion of meningeal and brain tissue through a skull-base defect. Here, we report three cases of anterior meningoencephalocele operated on one-stage procedure, a combined of transcranial and anterior approach, for invagination removal of non-functional extracranial cerebral tissue with watertight closure of the dural defect; written consent was taken. All cases were nasoethmoid, the congenital anomalies between the nasal bones and the nasal cartilage.
Keywords: Menigoencephalocele, Nasoethmoid, Transcranial and Anterior Resection